Centralized Conferencing in the IP Multimedia Subsystem: from theory to practice - A. Amirante; A. Buono; T. Castaldi; L. Miniero; S. P. Romano (Journal of Communications Software and Systems, 2008)
In this paper we present a conferencing architecture compliant with the IP Multimedia Subsystem (IMS) specification. To the purpose, we embrace a practical approach, by describing an actual implementation of an open source centralized video-conferencing system, called CONFIANCE, capable to offer advanced communication experience to end-users through the effective exploitation of mechanisms like session management and floor control. CONFIANCE has been designed to be fully compliant with the latest standard proposals coming from both the IETF and the 3GPP and can be considered as an outstandingexample of a real-time application built on top of the grounds paved by the SIP protocol. We will discuss in the paper both the design of the overall conferencing framework and the most important issues we had to face during the implementation phase.